A New Record of Domesticated Little Barley (Hordeum pusillum Nutt.) in Colorado: Travel, Trade, or Independent Domestication. Issue 4 (2nd October 2017) - Graham, Anna F.; Adams, Karen R.; Smith, Susan J.; Murphy, Terence M.
Abstract : Little Barley Grass ( Hordeum pusillum Nutt.) is a well-known native food domesticated in the U.S. Southwest by prehistoric Hohokam farmers in Central and Southern Arizona. This domesticated grass has recently been recovered from a late Basketmaker III community in southwestern Colorado, far from its well-known Hohokam region. Although travel or trade could explain this new Colorado record, we review morphological, ecological, and other types of evidence to consider a case for independent domestication. This case is supported by Old World molecular evidence for independent domestications of wild barley ( Hordeum spontaneum ) in both the Near East and Tibet. Simple mutations, frequent in nature, can produce wild plant populations of possible interest to humans. Supporting evidence exists in the form of larger than usual grass pollen grains. Supplemental plausibility arguments can include prior familiarity with the domestication process, and finding modern mutations such as free-threshing grains or larger-than-normal polyploid plants. Molecular assessments of modern populations can elucidate Little Barley relationships between major regions of North America, subregions of the U.S. Southwest, and uncharred archaeological specimens. This new Little Barley example presents evidence upon which such stories are crafted, and reveals the importance of native domesticates in ancient subsistence regimes.